2011
DOI: 10.1089/pho.2010.2984
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric and Microbiological Assessment of Photodynamic Therapy as an Adjuvant Treatment for Periodontitis: A Short-Term Evaluation of Inflammatory Periodontal Conditions and Bacterial Reduction in a Rat Model

Abstract: PDT used as an adjuvant treatment showed effective short-term control of periodontitis infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 43 publications
1
18
0
8
Order By: Relevance
“…After intraperitoneal anesthesia (ketamine chlorohydrate, 0.08 mL/100g body weight; xylazine chlorohydrate, 0.04 mL/100g), a thread of sterile 3-0 black silk (Johnson and Johnson) was placed (on both sides) around the cervix of each upper first molar and knotted mesially (13). The thread remained fully attached in a subgingival position in the cervical region.…”
Section: Ligature-induced Periodontal Diseasementioning
confidence: 99%
“…After intraperitoneal anesthesia (ketamine chlorohydrate, 0.08 mL/100g body weight; xylazine chlorohydrate, 0.04 mL/100g), a thread of sterile 3-0 black silk (Johnson and Johnson) was placed (on both sides) around the cervix of each upper first molar and knotted mesially (13). The thread remained fully attached in a subgingival position in the cervical region.…”
Section: Ligature-induced Periodontal Diseasementioning
confidence: 99%
“…The small radius of the effect of the cytotoxic chemically reactive molecules which are bactericidal yet safe for the host tissues makes PDT an exciting non‐invasive antimicrobial therapy with little probability of developing resistance . Animal studies have demonstrated absence of any toxicity for the surrounding host tissues including the healing connective tissues …”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial PDT combines a nontoxic photoactivatable dye or photosensitizer with harmless visible light of the correct wavelength to excite the dye to its reactive triplet state, which will then generate reactive oxygen species (ROS) such as singlet oxygen and hydroxyl radicals that are toxic to cells (9)(10)(11)(12). aPDT is an emerging alternative to treat localized infections (13)(14)(15), including oral diseases (16) such as periodontitis (13,(17)(18)(19), adjuvant approach for endodontic treatment (20,21) and caries (22,23).…”
Section: Introductionmentioning
confidence: 99%